The Influence of Price and Product Quality on Product Purchasing Decisions at Pt Intan Pariwara - Dewi Widhy Asti; Hasbiah, Siti; Wardhana Haeruddin, Muh. Ilham (Journal of Scientific Research, Education, and Technology (JSRET), 2022)
Dewi Widhy Asti. 2022. The Influence of Price and Product Quality on Product Purchase Decisions at PT. Pariwara Diamond. Supervisors: Siti Hasbiah and Muh. Ilham Wardhana Haeruddin. This study aims to determine: (1) the effect of price on product purchasing decisions at PT. Intan Pariwara Palopo Branch. (2) the effect of product quality on product purchasing decisions at PT. Intan Pariwara Palopo Branch. (3) the effect of price quality and product quality on product purchasing decisions at PT. Intan Pariwara Palopo Branch. The population in this study are consumers in 2019 - 2021 at PT. Intan Pariwara cab Palopo totaling 2,128,179 people. The sampling technique uses probability sampling technique. Data collection was carried out using a questionnaire method. The data analysis technique used is the classical assumption test and hypothesis testing with multiple linear regression analysis. The results of the research after the data were processed through the help of the SPSS program from data testing carried out by the results of the validity test and the results of the reliability test showed that the data used in this study were stated to be valid and reliable. Data testing is continued with the classical assumption test where from the results of the classical assumption test it can be stated that the data is normally distributed and the data used comes from the same (homogeneous) data. This is evidenced by the t test for the work experience variable which has a t_count > t_table value, that is, t count > t table, that is, 2.027 > 1.984 and a significance value of 0.012 <0.05 so it can be stated that the price variable has a partial effect on decisions purchase and Hypothesis acceptable. Then, price and product quality variables simultaneously influence the purchasing decision variable. The results of this study support the hypothesis which states that price and product quality simultaneously have a positive effect on purchasing decision.